2019
DOI: 10.1038/s41583-019-0152-2
|View full text |Cite
|
Sign up to set email alerts
|

Emerging connections between cerebellar development, behaviour and complex brain disorders

Abstract: The human cerebellum has a protracted developmental timeline compared to the neocortex, expanding the window of vulnerability to neurological disorders. As the cerebellum is critical for motor behavior, it is not surprising that most neurodevelopmental disorders share motor deficits as a common sequela. However, evidence gathered since the late 80's suggests that the cerebellum is involved in motor as well as non-motor function, including cognition and emotion. More recently, evidence indicates that major neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
221
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(230 citation statements)
references
References 253 publications
(286 reference statements)
3
221
1
5
Order By: Relevance
“…Furthermore, the role of the cerebellum is not limited to motor control 143 , as the cerebellar outputs influence cortical processing 144 , and mice lacking the autism-linked protein Tsc1 only in Purkinje cells exhibit abnormalities in social interaction 145 . Connections between the cerebellum and human neurologic disorders including autism spectrum disorders continue to grow 146 .…”
Section: Loss Of Function Of Fmrp Causes Altered Behavior and Cognitimentioning
confidence: 99%
“…Furthermore, the role of the cerebellum is not limited to motor control 143 , as the cerebellar outputs influence cortical processing 144 , and mice lacking the autism-linked protein Tsc1 only in Purkinje cells exhibit abnormalities in social interaction 145 . Connections between the cerebellum and human neurologic disorders including autism spectrum disorders continue to grow 146 .…”
Section: Loss Of Function Of Fmrp Causes Altered Behavior and Cognitimentioning
confidence: 99%
“…Elevated levels of anxiety are also linked to many neurological disorders such as ASD, ADHD, and postpartum depression. Compelling clinical evidence suggests that the cerebellum plays an important role in many psychiatric and neurodevelopmental disorders, such as schizophrenia, ADHD and ASD (Sathyanesan et al, 2019;Stoodley, 2016), presumably because of extensive connections between the cerebellum and brain regions involved in executive function, cognition and emotional control (D'Mello and Stoodley, 2015;Strick et al, 2009;Wang et al, 2014). Our results indicate that perturbation of the input layer of the cerebellum can elevate anxiety and stress, and this could contribute to all of these cerebellar-dependent behaviors.…”
Section: Increased Anxiety-like Behavior In Cb  Ko Micementioning
confidence: 56%
“…However, many studies have demonstrated that the cerebellum is not limited to motor functions but controls cognitive, social and emotional processes (Buckner, 2013;Schmahmann et al, 2019;Stoodley and Schmahmann, 2018;Strick et al, 2009). In addition, animal and clinical studies found that cerebellar disruption is a common feature of psychiatric and neurodevelopmental disorders such as schizophrenia, ADHD and ASD (Becker and Stoodley, 2013;Fatemi et al, 2012;Kloth et al, 2015;Sathyanesan et al, 2019;Stoodley et al, 2017;Tsai et al, 2012;. Thus, there is considerable overlap in the behavioral deficits and disorders that involve the cerebellum and GABA A Rs, suggesting that cerebellar GABA A Rs might contribute to diverse behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Both the thalamocortical system and the cerebellum have been implicated to undergo critical periods (Kivrak and Erzurumlu, 2013;Wang et al, 2014). Disruptions of the cerebellar development are suggested to cause disrupted behavioral traits in the motor and non-motor domain, linking to various neurodevelopmental disorders and psychiatric diseases, like autism spectrum disorder and schizophrenia (Wang et al, 2014;Sathyanesan et al, 2019). These neurological conditions are thought to be related to malformations in the neuronal wiring caused by adverse early life events (Di Martino et al, 2014;Nair et al, 2015) and our current study suggests that in the murine brain…”
Section: Timing Of Invasion In the Thalamusmentioning
confidence: 63%